Disseminação de Salmonella sp na cadeia produtiva do frango de corte - Mendonça, Eliane Pereira (2011)
The objective was to determine the antimicrobial resistance and to identify the ribotypes of 96 Salmonella strains isolated from poultry plants with complete production cycle to establish their profile dissemination. The highest percentages of resistance were to sulfonamide (56.25%), tetracycline (53.12%) and amoxicillin (31.25%), while 28.13% of the isolates were sensitive to all antibiotics tested. The profiles of multidrug resistance were observed in 28 strains (29.17%) of serovar Minnesota. In MIC were found strains at concentrations above the maximum (tetracycline >256 μg/mL - 7; sulfamethoxazole >1024 μg/mL - 45; amoxicillin >256μg/mL - 16). The ribotyping identified 63/96 strains. Of the samples tested, 21 were identified as Minnesota and grouped into six ribotypes, and the 208-S-8 was the most prevalent with 11 identifications (52.38%). Fourteen samples of S. Infantis were grouped into seven ribogroups, and the 337-S-2 was the most prevalent, 8/14 (57.14%). Two samples of S. Schwarzengrund and two S. Newport were grouped in the ribogroups 208-S-4 and 204-S-7, respectively. The multidrug resistance of S. Minnesota alert to the needing of implements systematic monitoring of antimicrobial resistance in zoonotic bacteria. The MIC above the maximum concentration suggests that these bacteria may have changed with the emergence of acquired resistance. The results emphasize the needing for responsible use of antibiotics in animal production, especially those used in human medicine. The high prevalence of ribogroup 208-S-8 (S. Minnesota) and 337-S-2 (S. Infantis) characterizes the clonal spread of these serovars, isolated from the farm until slaughter. These results indicate that positive birds at the farm contribute to contamination of carcasses at the slaughterhouse. The identification of clonal strains may establish the epidemiological link between isolates of Salmonella, thereby determining the stage of the chain of industrial production of broiler chickens that contributes to the contamination of the final product.